Spawning habitat selection in Schizothorax wangchiachii using acoustic tagging and tracking - Li, Bo; Hu, Fanxu; Li, Wenjing; Su, Wei; Zhu, Jiazhi; Jiang, Wei (Frontiers in Ecology and Evolution, 2025)
IntroductionAs a key protected species in the lower reaches of the Jinsha River, Schizothorax wangchiachii plays a vital role in maintaining aquatic ecosystem stability. Understanding habitat suitability conditions for its spawning grounds is critical for habitat restoration.MethodsTo systematically investigate habitat selection mechanisms and key drivers during its spawning period, this study induced its natural reproduction by enriching the natural habitat with diverse substrates, used acoustic telemetry to track movement trajectories, thereby clarifying environmental requirements.ResultsThe results showed that the S. wangchiachii exhibited significant aggregation during spawning (Z > 2.58, P < 0.01), mainly gathering in the slow-flow beach area which belonged to the shallow flow type of slow-flow habitats. Notably, environmental preferences diverged between spawning phases, S. wangchiachii exhibited divergent environmental preferences, which were categorized into two distinct habitat types: pre- and post-spawning stages favored habitats with slower surface velocities (0.10–0.25 m/s), shallower depths (0.43–0.66 m), and small-pebble substrates. Active spawning, however, occurred exclusively in nest-like depressions characterized by higher surface velocities (0.32–0.42 m/s), reduced bottom velocities (0.04–0.24 m/s), greater depths (0.52–0.71 m), and finer gravel substrates. Random Forest-based importance analysis indicated that fluvial substrate composition and surface flow velocity were the key predictive variables for habitat selection model with MeanDecreaseGini being 23.3% and 22.6%, respectively.SignificanceThese findings provide quantitative criteria for restoring natural spawning grounds and optimizing ecological operation strategies to support S. wangchiachii conservation in the lower Jinsha River.